Natural antioxidants from pineapple (Ananas comosus L.Merr.) byproducts stabilized by spray drying for food products - Lourenço, Ana Sofia Casanova (2021)
Doutoramento em Engenharia Alimentar / Instituto Superior de Agronomia. Universidade de Lisboa